IN THIS ISSUE (The Strategic Review for Southern Africa, 2020)
In line with the journal's specific focus on current policy issues of local and regional relevance this issue of the Strategic Review for Southern Africa offers you new insights on local, regional and continental matters from a variety of perspectives, with Zimbabwe and South Africa being the most prominent reference points.
Keywords: ZANU-PF; Zimbabwe; South Africa; Namibia; SWAPO; ANC; President Mugabe; Origin myth; Post-apartheid; African agenda; Responsibility to Protect; South Africa's Constitutional Court; Student protests; chimurenga; Strategic Review for Southern Africa; vol 39 no 2 November 2017